THE CONSTITUTIONAL DIMENSION OF OBSTRUCTION OF JUSTICE IN CORRUPTION CASES: A STUDY OF CONSTITUTIONAL JUSTICE CRISIS IN THE PT. TIMAH INDONESIA CASE: DIMENSI KONSTITUSIONAL OBSTRUCTION OF JUSTICE DALAM PERKARA KORUPSI: STUDI KRISIS KEADILAN KONSTITUSIONAL DALAM KASUS PT. TIMAH INDONESIA - Tiara Maharani; Ali Masyhar Mursyid (Constitutional Law Society, 2026)
The enforcement of anti-corruption law in Indonesia not only concerns the punishment of the main perpetrators but also the protection of the judicial process itself. One of the serious threats to the integrity of the judicial system is obstruction of justice, which interferes with the process of investigation, prosecution, and adjudication of corruption cases. Article 21 of the Indonesian Anti-Corruption Law regulates obstruction of justice as an independent offense intended to safeguard the judicial process. However, its practical enforcement often reveals inconsistencies that undermine constitutional justice. This article analyzes obstruction of justice from the perspective of constitutional law by positioning it as a constitutional offense that threatens the fundamental principles of the rule of law and judicial independence. Using a normative juridical method with constitutional, statutory, conceptual, and comparative approaches, this research examines the PT Timah corruption case, particularly the decision of the Pangkalpinang District Court concerning obstruction of justice committed by Toni Tamsil. The findings reveal a significant disparity between the normative framework of Article 21 of the Anti-Corruption Law and its application in judicial practice. The relatively light sentence imposed in the case reflects a broader crisis of constitutional justice in the enforcement of obstruction of justice in Indonesia. The study argues that obstruction of justice should be treated as a constitutional offense because it directly undermines the integrity of the judiciary, weakens anti-corruption efforts, and erodes public trust in the rule of law. Strengthening constitutional interpretation in the enforcement of obstruction of justice is therefore necessary to ensure the protection of judicial independence and the effectiveness of corruption eradication.